Perioperative Anaphylaxis: A Systematic Approach to Evaluate High-Risk Drug Allergy - Alexandra Navard-Keck; Stanislaw J. Gabryszewski; Emily S. Robbins; Joseph Cafone; Juhee Lee (Case Reports in Critical Care)
Determining the etiology of perioperative anaphylaxis is a challenging task, as multiple medications are often administered simultaneously during anesthesia. This is compounded by the paucity of validated skin testing. While drug challenges are the definitive means of assessing for IgE-mediated drug allergy, they must be weighed with the risk of severe reaction. As such, multidisciplinary collaboration is warranted to ensure drug provocation testing is performed thoughtfully and safely. Here, we present a case of an 18-year-old male with juvenile kyphosis who underwent anesthesia prior to spinal fusion surgery. He was given intravenous fentanyl, propofol, dexamethasone, remifentanil, tranexamic acid, methadone, and cefazolin. Additionally, iodine, chlorhexidine, and tincture of benzoin were applied topically. Shortly after the start of anesthesia and prior to incision, he developed bronchospasm, hypoxia, hypotension, and pulseless electrical activity with a return of spontaneous circulation following cardiopulmonary resuscitation. A tryptase level drawn during the event was elevated at 23.7 μg/L (reference range: 0–11.4 μg/L). Months later, the patient underwent skin prick and intradermal testing in an allergy clinic, which was largely unrevealing for a culprit. Given the absence of validated predictive values for skin testing, drug provocation testing was performed with the patient admitted to the intensive care unit due to the high-risk nature of testing. Medications were selected for a challenge after multidisciplinary discussions with specialists in anesthesia and surgery based on the availability of alternative medications. Following negative drug provocation testing to intravenous dexamethasone, intravenous fentanyl, oral midazolam, intravenous methadone, and intravenous tranexamic acid, as well as topical challenges to chlorhexidine, iodine, and tincture of benzoin, the patient was instructed to continue to avoid cefazolin, propofol, and remifentanil and was able to subsequently undergo spinal fusion surgery safely. This case demonstrates a systematic approach for high-risk drug allergy testing that was facilitated by collaboration with allergy, intensive care, anesthesia, and surgery.